Family Communication and Innovativeness in Family Firms. Issue 3 (4th June 2013) - Sciascia, Salvatore; Clinton, Eric; Nason, Robert S.; James, Albert E.; Rivera‐Algarin, Juan O.
<x xml:space="preserve">Abstract</x> This conceptual article seeks to address the heterogeneity of family firms in terms of their innovativeness by investigating business family communication dynamics. We use the established family communication constructs of conversation and conformity orientations to develop a typology of family firms in terms of innovativeness. We provide empirically testable propositions and present possible operationalizations for future research. In particular, we argue that supportive business families (i.e., families characterized by high conversation orientation and moderate conformity orientation) are associated with the highest levels of innovativeness in the family‐controlled firm. Through this article we hope to deepen our understanding of the relationship between family and firm levels of analysis, to develop a stronger bond between communication and innovative behavior, and to identify family‐related antecedents of heterogeneity in family firm innovativeness.